Validação de marcadores moleculares ligados à apomixia em Panicum maximum Jacq - Bluma-Marques, Anna Carolina (2013)
Apomixis is an assexual form of reproduction that results in seeds genetically identical to the mother plant. In the genebank of P. maximum at Embrapa Beef Cattle there are apomitic plants, all tetraploids, and sexual genotypes that experienced tetraploidization and enable breeding. The segregation of apomixis in the F1 progenies in the species is 1:1, and the techniques available to identify the mode of reproduction are time-consuming, laborious and often unviable for a big amount of samples. Searches have been made after techniques that can easily and quickly identify the mode of reproduction. Four potential RAPD markers linked to apomixis were identified in an F1 population of P. maximum, using the bulked segregant analysis (BSA) method. The aim of this research was to validate these molecular makers in two F1 populations determining their frequency of recombination between the markers and the apomixis locus to confirm if they are linked to this important characteristic. For this, the DNA of the hybrids and their genitors were extracted. Only hybrids with determined mode of reproduction were used. The population A had 75 hybrids obtained from the cross between the S10 (tetraploid sexual plant) and cultivar Tanzânia (tetraploids apomitic plant) and the population DE had 33 hybrids from the cross of S12 (tetraploid sexual plant) and cultivar Tanzânia. The four RAPD markers were amplified in the populations and presented mendelian segregation. The ligation analyses revealed co-segregation between the markers and apomixis in the two populations. A ligation map was constructed by the Kosambi function. The distance of the markers and the apomixis locus was of 12.0, 20.8, 18.6 and 18.6 cM in the population A, while for the population DE only two makers were used to create the map, their distance was of 9.1 and 15.6 cM. The selection efficiency of the markers was also calculated, and they varied from 90% to 72,2% in the two populations. These markers can be used in the determination of the mode of reproduction in P. maximum, assisting in the initial stages of breeding in the species and speeding the release of new cultivars in the market.